New reliability optimization solution in enterprise private voice line service based on multi-network collaboration - Yu WU; Xiaoyan WANG; Yun YANG; Hua WANG; Yan DOU; Jingjing FANG (Dianxin kexue)
The voice line based on VoIP and adopting PON access has become the mainstream solution for the enterprise private voice line service market.The traditional TDM voice line still retained the reliability advantage based on the SDH access.Therefore,a new VoIP line reliability optimization solution that didn’t rely on SDH and transmission protection technology was proposed.The lower cost and high efficiency of the solution was demonstrated and the specific method of the scheme was analyzed to achieve the networking goal through multi-network collaboration.Through both laboratory test and present network trial,the rationality,feasibility and stability of the solution was verified.